TIS Toruński Informator "Solidarności" . pismo RKW NSZZ "Solidarność" Regionu Toruńskiego, no. 177, 1987 - Cichoń, Wiesław; Spandowski, Roman; Kaczor, Andrzej; Sienkiewicz, Radek; Borek, Piotr; Musielak, Ryszard (s.n.], 1987)
Creation and circulation: From issue no. 10=227(1989)published legally